Three-dimensional printed embedded channel–based resistive strain sensor: Fabrication and experimental characterization. (June 2019) - Smith, Austin; Mofidian, SM Mahdi; Bardaweel, Hamzeh
This work explores the feasibility of commercially available elastic filament and desktop fused deposition modeling three-dimensional printing as a simple and cost-effective route to develop flexible sensors. The fabricated sensor consists of a three-dimensional printed flexible substrate with embedded U-shaped channels that are filled with Galinstan (Ga 68.5% In 21.5% Sn 10%) liquid metal conductor. When the sensor is strained, the cross-sectional area of the channels decreases causing a reduction in the conducting area and, therefore, a change in resistance. First, sensors measuring approximately 2100 μm by 200 μm are fabricated. Results demonstrate gauge factors of approximately 2.1 at 38.8% strain with high linearity and little hysteresis. In addition, smaller strain sensors, measuring approximately 696 µm by 203 µm, are fabricated with gauge factors of nearly 1.0 at 13.2% strain. Results show that substrate relaxation plays an essential role in determining the functionality of these sensors. The Mullins effect largely influences the recovery properties of the rubber-like sensor substrate. This leads to a noticeable relaxation in the substrate during cyclic loading. The results demonstrate the potential of commercially available fused deposition modeling three-dimensional printing technology and filaments to produce complex designs and sensor platforms.